1997
DOI: 10.1038/sj.bmt.1700750
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the effects of high-dose chemotherapy and bone marrow transplantation on sexual function in the first year after transplant

Abstract: Summary:We have initiated a long-term prospective study of sexual function using the Derogatis Interview for Sexual Functioning (DISF) for males and females. 8 This self-adminisPatients undergoing high-dose chemotherapy and bone marrow transplantation (BMT) may experience a vartered questionnaire has a number of advantages. It is widely used, easy to administer and well validated in cancer iety of abnormalities of psychological and physical function including sexual dysfunction. However, no study patients. 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…First, sexual dysfunction in the form of lack of desire, body image problems and physical functioning is a salient issue for patients undergoing BMT. This finding is consistent with previous studies that have examined sexual functioning specifically [7][8][9][10] or as part of a larger quality of life assessment in BMT recipients. [1][2][3][4][5][6] Compared to a previous study 10 of sexual functioning that included baseline, 1-and 3-year time points, our participants reported more sexual difficulties pretransplantation in terms of orgasm (14 vs 46% for women; 4 vs 13% for men) vaginal dryness (30 vs 49%), erectile dysfunction (13 vs 33%) and painful intercourse for women (14 vs 29%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…First, sexual dysfunction in the form of lack of desire, body image problems and physical functioning is a salient issue for patients undergoing BMT. This finding is consistent with previous studies that have examined sexual functioning specifically [7][8][9][10] or as part of a larger quality of life assessment in BMT recipients. [1][2][3][4][5][6] Compared to a previous study 10 of sexual functioning that included baseline, 1-and 3-year time points, our participants reported more sexual difficulties pretransplantation in terms of orgasm (14 vs 46% for women; 4 vs 13% for men) vaginal dryness (30 vs 49%), erectile dysfunction (13 vs 33%) and painful intercourse for women (14 vs 29%).…”
Section: Discussionsupporting
confidence: 82%
“…Most studies of sexual functioning have used short follow-up periods (3-12 months) or have been cross-sectional in nature. [7][8][9] Among those studies that have been published, only one went beyond a 1-year follow-up. 10 In that study, sexually active survivors completed measures of sexual activity, sexual problems (i.e., arousal, orgasm) and sexual satisfaction 1-and 3-years post transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual problems were reported by 24% of treated Hodgkin's disease patients studied by Kornblith et al (1992) and less interest in sexual activity was reported by 20% of a similar group studied by Fobair et al (1986). Rates of sexual dysfunction following BMT have been described in between 20 and 50% of patients (Hjermstad and Kassa, 1995;Marks et al, 1997). Testosterone is important for determining sexual desire and erectile function and will therefore impact on sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][22][23][24][25][26][27][28][29][30][31] The majority of these, 4 each, came from the United States and the United Kingdom, 2 from Germany and 1 each from Canada, Ireland, The Netherlands and Finland.…”
Section: Resultsmentioning
confidence: 99%
“…6,8,9,27,30 Case-matched controls were used in four studies. 8,27,28,30 Eight studies focused primarily on sexuality and sexual dysfunction, [6][7][8][9]22,26,27,29 and five studies focused primarily on QOL/late effects, with a secondary focus on sexual function. [23][24][25]28,30,31 The type of HSCT was allogeneic in five studies, autologous in two and both allogeneic and autologous in six studies.…”
Section: Research Design and Purposesmentioning
confidence: 99%